2019
DOI: 10.1038/s41598-019-45314-9
|View full text |Cite
|
Sign up to set email alerts
|

First-principles calculations of the epsilon phase of solid oxygen

Abstract: The crystal, electronic and magnetic structures of solid oxygen in the epsilon phase have been investigated using the strongly constrained appropriately normed (SCAN) + rVV10 method and the generalized gradient approximation (GGA) + vdW-D + U method. The spin-polarized SCAN + rVV10 method with an 8-atom primitive unit cell provides lattice parameters consistent with the experimental results over the entire pressure range, including the epsilon-zeta structural phase transition at high pressure, but does not pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…An X-ray diffraction study (6,8) indicates that the zeta phase is stiffer than the epsilon phase. This is also consistent with the recent calculation (16).…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…An X-ray diffraction study (6,8) indicates that the zeta phase is stiffer than the epsilon phase. This is also consistent with the recent calculation (16).…”
Section: Resultssupporting
confidence: 94%
“…The first interpretation implies that the change in compressibility at the metallization pressure is similar to the behavior of the continuum band, which is described later in this paper. The second interpretation derives that the electronic structure changes not only in the a-b plane, as reported in the theoretical studies (15,16), but also parallel to the c axis (i.e., O 2 molecular axis) in the metallization.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…We note that the newly-proposed SCAN-rVV10 functional is one of the strongly constrained and appropriately normed metageneralized gradient approximation (meta-GGA) functionals that is considered to model well metallic, insulating and semiconducting materials (Sun et al, 2015;Sun J. et al, 2016;Buda et al, 2017). The rVV10 part of the functional accounts for the non-local correlation part required to appropriately describe van der Waals (vdW) interaction (Peng et al, 2016;Chakraborty et al, 2018;Zhang et al, 2018;Anh et al, 2019). Bokdam et al have demonstrated that the SCAN functional accounts for short range dispersion effects-which conventional hybrid functionals do not account for-and is the most suitable functional to study the atomic structure of hybrid perovskite materials (Bokdam et al, 2017).…”
Section: Computational Detailsmentioning
confidence: 99%